Apelin Is a Prototype of Novel Drugs for the Treatment of Acute Myocardial Infarction and Adverse Myocardial Remodeling - Sergey V. Popov; Leonid N. Maslov; Alexandr V. Mukhomedzyanov; Boris K. Kurbatov; Alexandr S. Gorbunov; Michail Kilin; Viacheslav N. Azev; Maria S. Khlestkina; Galina Z. Sufianova (MDPI AG, 2023)
In-hospital mortality in patients with ST-segment elevation myocardial infarction (STEMI) is 5-6%. Consequently, it is necessary to develop fundamentally novel drugs capable of reducing mortality in patients with acute myocardial infarction. Apelins could be the prototype for such drugs. Chronic administration of apelins mitigates adverse myocardial remodeling in animals with myocardial infarction or pressure overload. The cardioprotective effect of apelins is accompanied by blockage of the MPT pore, GSK-3β, and the activation of PI3-kinase, Akt, ERK1/2, NO-synthase, superoxide dismutase, glutathione peroxidase, matrix metalloproteinase, the epidermal growth factor receptor, Src kinase, the mitoKATP channel, guanylyl cyclase, phospholipase C, protein kinase C, the Na+/H+ exchanger, and the Na+/Ca2+ exchanger. The cardioprotective effect of apelins is associated with the inhibition of apoptosis and ferroptosis. Apelins stimulate the autophagy of cardiomyocytes. Synthetic apelin analogues are prospective compounds for the development of novel cardioprotective drugs.